OP0253 The JAK Inhibitor Tofacitinib Suppresses Synovial JAK1-STAT1 Signalling in Rheumatoid Arthritis. (23rd January 2014) - Boyle, D. L.; Wei, N.; Singhal, A. K.; Rosengren, S.; Kaplan, I.; Soma, K.; Hodge, J.; Luo, Z.; Krishnaswami, S.; Gruben, D.; Zwillich, S. H.; Bradley, J.; et al.
Abstract : Background: Tofacitinib is a novel oral Janus kinase (JAK) inhibitor for the treatment of rheumatoid arthritis (RA). The specific JAK-STAT (signal transducer and activator of transcription) pathways affected by tofacitinib and the downstream effects on gene expression in situ are not known. Objectives: To understand how tofacitinib alters synovial biology in RA, we performed a prospective serial synovial biopsy study. The effects of JAK inhibition on synovial histopathology, gene expression, and signalling were determined and correlated with clinical response. Methods: A randomised, double-blind, Phase 2a clinical trial (A3921073; NCT00976599 ) of seropositive RA patients (pts) with inadequate response to methotrexate compared tofacitinib 10 mg twice daily (BID) for 1 month (15 pts) with placebo (PBO; 14 pts). Synovial biopsies were performed on Days -7 and 28. Biopsies were analysed by immunohistochemistry (IHC), real-time polymerase chain reaction (PCR), and synovial tissue extracts by enzyme-linked immunosorbent assay. Clinical response was determined by disease activity score (DAS)28-4 (erythrocyte sedimentation rate) and EULAR criteria. Results: Exposure to tofacitinib led to EULAR moderate to good responses (11/14 pts), while PBO was ineffective (1/14 pts) on Day 28. Tofacitinib treatment significantly reduced synovial mRNA expression of the matrix metalloproteases MMP1 and MMP3 (p<0.05), and chemokines CCL2, CXCL10, and CXCL13 (p<0.05). No overall changes were observed in synovial inflammation scores or the presence of any immune cell lineages at this time point using IHC e.g. CD20, CD3, CD68 (B cells, T cells and macrophages, respectively), as well as quantitative PCR to quantify cell specific genes e.g. CD19, CD3 (B cell, T cell, respectively). Clinical responses in the tofacitinib-treated group correlated with several synovial biomarkers e.g. mean pSTAT1 levels were significantly decreased (p<0.05) in tofacitinib responders (48%) but not in PBO non-responders (21%). In contrast, only a trend towards a modest decrease in pSTAT3 was observed with tofacitinib responders. Tofacitinib (bound plus unbound) peak and trough serum levels were approximately 290 nM and 30 nM, respectively; these drug exposures are within the half-maximal inhibitory concentration (IC50) range required to block STAT1 phosphorylation in T cells (54 nM), but below the IC50 for STAT3 phosphorylation (367 nM). Conclusions: The data suggest that tofacitinib modulates synovial immune and inflammatory responses by suppressing JAK1-STAT1 signalling, and that these changes correlate with clinical response. The greater effect on STAT1 vs STAT3 is likely due to greater sensitivity of this pathway to tofacitinib inhibition and the serum concentrations achieved with tofacitinib 10 mg BID. The STAT1 pathway is critical for interleukin-6 and interferon (IFN) signalling, with the latter effect paralleling reductions in expression of IFN-regulated chemokines (e.g. CXCL10 and CCL2) in the blood and synovium of tofacitinib-treated pts. The data suggest that the rapid clinical efficacy observed in tofacitinib-treated RA pts might be attributed, in part, to STAT1-related signalling events. Disclosure of Interest: D. Boyle Grant/research support from: Pfizer Inc., N. Wei: None Declared, A. Singhal : None Declared, S. Rosengren: None Declared, I. Kaplan Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., K. Soma Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Hodge Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., Z. Luo Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., S. Krishnaswami Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., D. Gruben Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., S. Zwillich Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Bradley Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., G. Firestein Consultant for: Pfizer Inc.